Banking Hegemony over the State Civil Apparatus: Gramsci's Analysis of Decree-Based Credit Culture in the Perspective of Islamic Economics - Muhammad Taufik Rahman; Desi Erawati; Siswandi; Hendra (Jurnal Hadratul Madaniyah, 2026)
Banking credit practices using the Decree of Appointment as collateral have become a systemic phenomenon among State Civil Servants in Indonesia. This study aims to analyze how the SK-based credit mechanism operates as an instrument of banking hegemony that normalizes debt in the lives of ASN and reviews this phenomenon through an Islamic economic perspective. Using a qualitative method with a literature study approach and critical analysis, this research dissects the power relations between banking institutions and ASN using Antonio Gramsci's theory of hegemony. The research findings indicate that banks, particularly Regional Development Banks, exercise hegemony through "voluntary consent" built on narratives of financial ease and consumptive lifestyles. The ASN SK is no longer just an administrative staffing document but has transformed into an economic commodity that shackle productivity and financial independence. From an Islamic economic perspective, this practice is criticized for containing ribawi elements, encouraging israf (excessive) behavior, and contradicting the principles of Maqashid Shariah, specifically in the aspect of hifzh al-mal (protection of wealth). The novelty of this research lies in the synthesis between Gramscian socio-political critique and Islamic economic axiology in dissecting ASN debt dependence. The implications of the study suggest the need for policy reform in financial literacy and the strengthening of sharia financing models that are more equitable for ASN.